COPD: misuse of inhaler devices in clinical practice - Araújo, António Duarte (2019)
Background and objectives: Inhalers mishandling remain an important clinical issue worldwide. The aim of this study was to evaluate inhalation technique in stable COPD out-patients. The variables under study were type of inhaler device (ID), patients' preference for an inhaler, number of IDs used by each patient, beliefs about inhaler medication and some demographic, clinical and functional patients' characteristics. We aim to assess how they are related to inhalation technique. Methods: A cross-sectional study was conducted in a hospital outpatient respiratory care. COPD patients over 40 years old, diagnosed according to GOLD criteria, and using IDs were included consecutively. The Beliefs about Medicines Questionnaire (BMQ), a demographic and a clinical survey were applied. The number of IDs used by each patient and the patients' preference for some IDs were recorded. Patients were asked to demonstrate the use of their prescribed inhalation devices, and inhaler technique was assessed by using previously defined checklists, including essential steps and critical errors. A statistics analysis was then performed. Results: We studied 300 subjects performing a total of 521 inhalation manoeuvers with 10 different IDs. At least one step incorrectly performed was found in 48.2% of demonstrations and in 29.9% critical errors were observed. Misuse was related to priming/loading in 6.9%, to inhalation manoeuver in 13.1% and to both in 10%. There was a statistically significant association between critical errors and type of ID (P<0.001). No significant relationship was found between correct performance of key manoeuvers and patients' preference or number of inhalers used per patient. Misuse due to critical errors was observed in 39.3% of patients and was positively related to female gender, age ≥65, lower education level and lower socioeconomic status (higher Graffar classification score), but not to patients' clinical or functional characteristics. In the sub-group of patients presenting critical errors when using IDs, there was a statistically significant inverse association between BMQ Necessity score and number of critical errors. Conclusions: Inhalers mishandling remains disappointingly common. A good inhalation technique depends on the type of ID, and failure of inhalation manoeuver was the main cause of ID misuse. It was not associated to multiple inhalers' use nor to patient's preference, but to the patient's beliefs about the necessity to use them. Elderly patients, women and those with lower education level or lower socioeconomic status demonstrate a worse inhalation technique.